소음에 대한 지식, 태도 및 실천이 청력손실에 미치는 영향 - 함완식; 이광묵; 황병문; Ham, Wan-Shik; Lee, Kwang-Mook; Whang, Byoung-Moon (한국산업위생학회지, 1999)
In order to evaluate the effects of knowledge, attitude and practice on noise-induced hearing loss or hearing threshold level, questionnaire survey was performed and hearing thresholds of 1 kHz and 4 kHz were measured on 1,040 subjects with workers exposed to noise, safety and health officers. industrial hygienists, analysts rind office workers. The results were as follows ; 1. The following 6 factors were obtained by factor analysis and factor rotation of 30 questionnaire of knowledge, attitude and practice about noise; knowledge of noise (F1), concern of hearing protective devices (F2), concern of noise induced hearing loss (F3), concern of noise level and hearing impairment (F4), concern of noise in workplace (F5) and recognition of noised-induced hearing loss (F6). 56.1% of variance was explained by 6 factors. 2. Significant variables influencing knowledge, attitude and practice about noise were education level and age in F1, personal protective devices (PPE) and education level in F2, age and education level in F3, education level, age and sex in F4, PPE, education level, age and work duration in F5, and work duration and PPE in F6. 3. Hearing thresholds of 4 kHz were significantly higher in workers exposed to noise than that of in the other subjects and tended to be higher in industrial hygienists, safety and health officers and analysts than that of the office workers. 4. Significant variables influencing hearing thresholds of 1 kHz were age, education level, F5 and F6 in workers exposed to noise, and F1 in industrial hygienists. 5. Significant variables influencing hearing thresholds of 4 kHz were age, F6, sex, work duration, F1, F5, F2 and F3 in workers exposed to noise, F1 and age in safety and health officers, and F6, sex and F4 in industrial hygienists. With the above results, it suggested that workers exposed to noise be needed the education of knowledge, attitude and practice about noise in hearing conservation program for the prevention of noise induced hearing loss. Also, it suggested that health managers in workplace be needed countermeasures to prevent hearing loss although they are intermittently exposed to noise.